Silent serial sensations : the Wharton brothers and the magic of early cinema - Lupack, Barbara Tepa (Cornell University Press, 2020)
"Filmmakers Ted and Leo Wharton, whose serials became popular in the 1910s, established a model for incremental storytelling and holdover suspense still employed by filmmakers and television producers more than a century later"--